Diverticulosis of the small bowell, intraoperative finding - Salada, Rocío; Tasende, Laura; Gómez del Valle, María José (Cirugía del Uruguay, 2021)
Diverticulosis can occur in any part of the digestive tract. The topography of the small intestine is infrequent, it occurs mainly at the level of the jejunum and in 35% of cases it is associated with colonic diverticulosis. It is more common in people over 40 years of age. The diverticula decrease in size and number towards the distal sector. Usually the diagnosis is incidental, however, complications can occur, of which gastrointestinal bleeding and diverticulitis are frequently highlighted. It is suggested that dietary fiber deficiency would generate abnormalities in intestinal peristalsis, which together with pseudo-obstructive phenomena and high intraluminal pressure, would act in areas of focal weakness causing injury. We present the case of an 88-year-old patient with a colon occlusion who underwent Hartmann surgery. During the intraoperative period, jejunal diverticula were identified without complications.